THE INFLUENCE OF PSYCHOLOGICAL CAPITAL, ORGANIZATIONAL SUPPORT, AND TRUST IN SUPERVISOR ON WORK ENGAGEMENT OF BRANCH GAS STATION MANAGERS IN A PETROLEUM COMPANY - Phiengsoontorn, Napaporn; Akakulanan, Sayamon (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to: 1) study the level of psychological capital, organizational support, trust in supervisor, and work engagement of branch gas station managers in a petroleum company; and 2) study the influence of psychological capital, organizational support, and trust in supervisor on work engagement of branch gas station managers in a petroleum company. This was quantitative research. The population comprised 1,100 gas station managers of petroleum companies, while the sample group consisted of 285 branch gas station managers selected through stratified random sampling. The research tools consisted of a personal data form, psychological capital questionnaire, organizational support questionnaire, trust in supervisor questionnaire, and work engagement questionnaire. Statistical methods were percentage, mean, standard deviation, correlation coefficient analysis, and multiple regression analysis with a stepwise method. The results indicated that: 1) branch gas station managers in a petroleum company had an overall psychological capital at a high level, in part of self - efficacy, optimism, hope, and resilience were at high levels; branch gas station managers in a petroleum company had organizational support and trust in supervisors at fairly high levels; branch gas station managers in a petroleum company had work engagement at a high level. 2) psychological capital in part of self - efficacy, optimism, resilience, and organizational support could jointly predict 62.8 % of work engagement of branch gas station managers in a petroleum company at .01 level of statistical significance.